Characterization and Quantification of Luteolin-Metal Complexes in Aqueous Extract of Lonicerae Japonicae Flos and Huangshan Wild Chrysanthemum - Weilan Cai; Yunhao Xiong; Manman Han; Zhimin Li; Liang Peng; Hongyi Zhang; Qin Zou; Lin Wu; Qingling Ye; Linfeng Liao (International Journal of Analytical Chemistry)
Luteolin is a flavonoid compound widely found in vegetables, fruits, and medicinal plants. In this study, the reaction conditions for luteolin and five metal ions (Ca2+, Mg2+, Zn2+, Fe3+, and Cu2+) to form complexes in hot water were optimized, which was at a molar ratio of 1 : 1 for luteolin and metal ions at 90°C in a volume of 20 mL for 2 h, and the ability of luteolin to form complexes with Cu2+ was the strongest. The DPPH scavenging test showed that luteolin exerted a dose-dependent effect on the clearance of free radicals; luteolin-Cu2+ complexes and luteolin-Fe3+ complexes accentuated the clearance of free radicals. Furthermore, we used high performance liquid chromatography (HPLC) to analyze luteolin in samples from two medicinal plants, obtained from the dissolution of aqueous extracts in two different solvents. The results showed that the peak areas for luteolin in the samples dissolved in 20% formic acid-methanol were significantly larger than those from the samples dissolved in methanol alone, with increases in the peak area being 135.6% (Lonicerae Japonicae Flos), and 161.16% (Huangshan wild chrysanthemum). The aforementioned results indicate that complexes formed from organic compounds and metal ions are present in the decoction of a plant.